2012
DOI: 10.2223/jped.2196
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of neonatal morbidity and mortality in late-preterm newborn infants

Abstract: Objective: To compare mortality and the principal intercurrent clinical conditions suffered by late-preterm newborn infants born with gestational ages of 34 full weeks to 36 weeks and 6 days, and full term newborns.Methods: This was a cross-sectional study of all preterm newborn infants born at a public hospital from August 2010 to August 2011. The study sample comprised late-preterm infants (cases) and a group of full term newborns (controls). Three controls were enrolled for each case. Maternal, gestational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 34 publications
5
32
0
12
Order By: Relevance
“…Preterm infants experience higher rates of respiratory distress syndrome, bronchopulmonary dysplasia, necrotising enterocolitis, kernicterus, hypoglycaemia, periventricular leucomalacia, seizures, intraventricular haemorrhage, cerebral palsy, infections, feeding difficulties, hypoxic ischaemic encephalopathy, retinopathy of prematurity, as well as visual and hearing loss. [5][6][7][8][9][10][11][12][13][14][15][16] Preterm birth and its sequelae can have significant negative psychosocial and financial impacts on families of preterm newborns. [17][18][19][20] While the risks of mortality and morbidity affecting preterm newborns are considerably more frequent at lower gestational ages, 11 late preterm infants (sometimes called 'near-term') still experience significantly higher risks compared with babies born at term.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…Preterm infants experience higher rates of respiratory distress syndrome, bronchopulmonary dysplasia, necrotising enterocolitis, kernicterus, hypoglycaemia, periventricular leucomalacia, seizures, intraventricular haemorrhage, cerebral palsy, infections, feeding difficulties, hypoxic ischaemic encephalopathy, retinopathy of prematurity, as well as visual and hearing loss. [5][6][7][8][9][10][11][12][13][14][15][16] Preterm birth and its sequelae can have significant negative psychosocial and financial impacts on families of preterm newborns. [17][18][19][20] While the risks of mortality and morbidity affecting preterm newborns are considerably more frequent at lower gestational ages, 11 late preterm infants (sometimes called 'near-term') still experience significantly higher risks compared with babies born at term.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…11,12 It was observed in this study a prevalence of NBs with high underweight, extreme premature and small for the gestational age (SGA). Similar results to the current study were found in a survey conducted in Maceió-AL, in which were found 29 (76.3%) premature NBs and 11 (28.9%) underweight.…”
Section: Discussionmentioning
confidence: 59%
“…Sabemos que os RNPTs possuem maiores fatores de risco para o desenvolvimento devido ao baixo peso, pouca idade gestacional, maiores déficits respiratórios e condições clínicas desfavoráveis. Entretanto, o recém-nascido pré-termo tardio (RNPT-T), representando bebês entre idade gestacional de 34 a 36 semanas, pode apresentar um risco de morbimortalidade quando comparados aos recém-nascidos a termo (15,16) . nascimentos prematuros e 8,5% de todos os nascimentos.…”
Section: Contextualização Do Recém-nascido Pré-termo Tardio (Rnpt-t)unclassified
“…nascimentos prematuros e 8,5% de todos os nascimentos. (15,(17)(18)(19) A etiologia, segundo Engle et al (20) , ainda não é muito bem definida, entretanto, os autores apontam para duas possíveis hipóteses 1) aumento no número de tecnologias assistidas, resultando em gravidez múltiplas 2) avanços na área obstétrica levando a um aumento nas intervenções médicas durante a gestação.…”
Section: Contextualização Do Recém-nascido Pré-termo Tardio (Rnpt-t)unclassified
See 1 more Smart Citation